2015
DOI: 10.1097/jom.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Exposure-Response Relationship of Particulate Matter and Mortality

Abstract: Our findings indicated that, at least in China, the PM10 pollutant has threshold effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…The curve was relatively steep at low levels and flattened out at higher exposures. Previous studies also found similar pattern under different levels of particulate matter [20, 23, 24]. However, considering there were few observations for PM 2.5 , cautions should be taken when using the estimations in the high concentration level.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The curve was relatively steep at low levels and flattened out at higher exposures. Previous studies also found similar pattern under different levels of particulate matter [20, 23, 24]. However, considering there were few observations for PM 2.5 , cautions should be taken when using the estimations in the high concentration level.…”
Section: Discussionsupporting
confidence: 51%
“…The concentration of PM 2.5 with the lowest AIC value was selected as the turning point. Similar method had been used in previous studies [1820]. According to the turning point (128 μg/m 3 ), we created two variables (high concentration level, low concentration level), which were higher or lower than the turning point respectively, to explore the piecewise linear association of PM 2.5 .…”
Section: Methodsmentioning
confidence: 99%
“…Combining our results from the base model with the aforementioned evidence, it would be better to control for the effect of temperature (and humidity) for at least for 7 days in order to adequately capture the heat effects and somewhat the cold effects, but extending the lags up to 21 days might sufficiently control for the overall cumulative temperature effects, including the prolonged cold effects, and the lag period of 21 days is also commonly adopted in studies of temperature-related mortality [12,26,34]. In addition, though the changes in the size of effects were small among the different extensive adjustments, we found that the observed roughly linear trend in curves in the whole population and subgroups became more evident and the plateaus or bumps seem less apparent after the extensive adjustments for temperature, especially for 21 days, which reminds us to interpret with caution the previously reported nonlinearity of the threshold relation for PM 10 with mortality in several Chinese cities [47], where the temperature were only modeled for days within one week, for which might be artifacts of inadequately controlled temperature and humidity. However, our results were based on a single city, so cautions still should be taken when the findings of the present investigation are generalized to other sites.…”
Section: Discussionsupporting
confidence: 50%
“…As a major atmospheric pollutant, fine particulate matter (PM 2.5 , defined as particle less than 2.5 mm aerodynamic diameter) has a small size and a relatively large surface area, which makes it easy to absorb viruses in the air. Especially considering the high levels of PM 2.5 pollution in Beijing [ 45 , 46 ], it is plausible that high wind velocity is a risk factor for the spread of HFMD. On the other hand, children spend more time with indoor activities in confined spaces during windy periods, which would increase the chances of EV transmission, a possible indirect explanation supporting the association of increased transmission with windy conditions.…”
Section: Discussionmentioning
confidence: 99%